Simple variants of non-cooperative polymorphic P systems - Kuczik, Anna; Vaszil, György (Journal of membrane computing, 2024)
We investigate the computational power of non-cooperative polymorphic P systems with no additional ingredients. The variants we study are even more simple in the sense that the sets of possible right-hand sides of the dynamically changing rules are finite. We show that systems with this type of restriction characterize exactly the class of Parikh sets of ET0L languages.